Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { 3 x } { 4 } - \dfrac { 2 x + 1 } { 3 }$
$y = 1$
$x$Intercept
$\left ( 4 , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 1 } { 3 } \right )$
$\dfrac{ 3x }{ 4 } - \dfrac{ 2x+1 }{ 3 } = 1$
$x = 16$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { 3 x } { 4 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 x + 1 } { 3 } } = \color{#FF6800}{ 1 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right ) \color{#FF6800}{ - } \left ( \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) \right ) = \color{#FF6800}{ 12 }$
$3 \left ( 3 x \right ) - \left ( \color{#FF6800}{ 4 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) \right ) = 12$
 Multiply each term in parentheses by $4$
$3 \left ( 3 x \right ) - \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \right ) = 12$
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right ) - \left ( 4 \times 2 x + 4 \right ) = 12$
 Get rid of unnecessary parentheses 
$\color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ x } - \left ( 4 \times 2 x + 4 \right ) = 12$
$\color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ x } - \left ( 4 \times 2 x + 4 \right ) = 12$
 Simplify the expression 
$\color{#FF6800}{ 9 } \color{#FF6800}{ x } - \left ( 4 \times 2 x + 4 \right ) = 12$
$9 x - \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 4 \right ) = 12$
 Simplify the expression 
$9 x - \left ( \color{#FF6800}{ 8 } \color{#FF6800}{ x } + 4 \right ) = 12$
$9 x \color{#FF6800}{ - } \left ( \color{#FF6800}{ 8 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \right ) = 12$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$9 x \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } = 12$
$\color{#FF6800}{ 9 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } - 4 = 12$
 Calculate between similar terms 
$\color{#FF6800}{ x } - 4 = 12$
$x \color{#FF6800}{ - } \color{#FF6800}{ 4 } = 12$
 Move the constant to the right side and change the sign 
$x = 12 \color{#FF6800}{ + } \color{#FF6800}{ 4 }$
$x = \color{#FF6800}{ 12 } \color{#FF6800}{ + } \color{#FF6800}{ 4 }$
 Add $12$ and $4$
$x = \color{#FF6800}{ 16 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture